The Multiplier Mirage: The Political Economy Of Public Procurement And Fiscal Centralization in Indonesia’s 2026 State Budget - Syahrul Salam (Journal of Tourism Economics and Policy, 2026)
The 2026 Indonesian State Budget (APBN) represents a profound paradigm shift in the nation’s fiscal strategy, departing from two decades of progressive decentralization in favor of a highly centralized, front-loaded expenditure model. This pivot is primarily operationalized through two massive socioeconomic initiatives: the Free Nutritious Meal (Makan Bergizi Gratis – MBG) program and the consolidation of subsidized goods distribution via the Red and White Village Cooperatives (Koperasi Desa Merah Putih – KDMP). Grounded in the theoretical promise of leveraging the demographic dividend to maximize government spending multipliers, these programs aim to stimulate regional economies and mitigate deflationary pressures inherited from early 2025. However, early implementation reveals a macroeconomic paradox: unprecedented state expenditure coexisting with stagnant domestic aggregate demand and regional liquidity starvation. This paper utilizes a political economy framework to analyze this discrepancy, conceptualized here as the "multiplier mirage." By examining the mechanisms of public procurement, this study identifies severe institutional bottlenecks characterized by both active waste (rent-seeking and opaque vendor appointments) and passive waste (administrative centralization and supply chain monopolization). Anchored in foundational literature on fiscal multipliers in developing nations and the mechanics of state clientelism, the analysis concludes that bypassing transparent e-procurement systems and crowding out local agricultural supply chains effectively extracts wealth from the regions rather than stimulating them. The paper argues that without immediate structural reforms—specifically, mandatory open electronic contracting and the enforcement of localized sourcing quotas—the intended fiscal stimulus will continue to be intercepted by systemic inefficiencies, ultimately jeopardizing Indonesia’s macroeconomic stability.